Effects of Internet Use And Reproductive Knowledge Sexual Education in Adolescents in Preventing Sexual Violence - Deni Nasir Ahma; Sumiah Nasution; Muhammad Arifin (Conference Series, 2020)
Intention of activity of research is to : a. knowing how big the influence of usage of internet to education of sexual at adolescent in preventing action hardness of sexual b. knowing how big influence of knowledge of reproduction to education of sexual at adolescent in preventing action hardness of sexual c. knowing collective influence of usage of internet and knowledge of reproduction to education of sexual at adolescent in preventing action hardness of sexual. Research method which is used in doing activity of research that is a survey method. Sample in research amounts to 100 responder people from 4 senior high school districts of Jagakarsa, Jakarta South. In acquirement of research result by using question instrument to know influence of usage of internet and knowledge of reproduction to education of sexual is adolescent.Technique analyse data descriptively analysis to obtain;get information is there any influence of usage of internet and knowledge of reproduction to education of sexual at adolescent in preventing to act hardness of sexual. Result from research namely a. existence of influence between usage of internet to education of sexual at adolescent in preventing to act hardness of sexual where almost more than 60 % adolescent often use internet and education of sexual of old fellow, society and school share equal to 57%. b. existence of influence between knowledge of reproduction to education of sexual at adolescent in preventing to act hardness of sexual where more than 60 % acquirement of information of the book and internet and education of sexual of old fellow, society and school share equal to 57 c. existence of influence collectively between usage of internet and knowledge of reproduction to education of sexual at adolescent in preventing action hardness of sexual namely equal to more than 50 %. Conclusion : a. Usage of Affect internet education of sexual at adolescent seen from often use and internet of situs which is often used by education of sexual at adolescent both for done from x'self a adolescent and also from outside myself a is adolescent ( old fellow, society and school) in preventing to act hardness of seksual.b. Knowledge of obtained reproduction from various source influence education of sexual at adolescent both for done from x'self a adolescent and also from outside myself a is adolescent ( old fellow, society and school) in preventing to act hardness of sexual. c. Together usage of the internet and knowledge of reproduction influence education of sexuality at adolescence in preventing the hardness of sexuality.